Component comparison based information quality assurance. (27th December 2007) - Zuo, Yanjun
This paper describes a model to assess the quality of available information objects. If two (or more) objects share similar attribute values but their values are calculated through significantly different methods or using highly similar methods independently, then those objects should be more trustworthy than if they are evaluated separately. Identifying such patterns provides 'multiple-proof' towards the correctness of the similar results those objects represent. Graph isomorphism technique is used to evaluate how similarly or differently two given objects have been constructed. The objective is to better evaluate the trustworthiness of given objects and provide quality assurance for information consumers.